REKONSTRUKSI KEWENANGAN KPU DALAM MENENTUKAN DAERAH PEMILIHAN DAN ALOKASI KURSI DPR RI DAN DPRD PASCA PUTUSAN MAHKAMAH KONSTITUSI NO 80/PUU-XX/2022 - Nurlaili Rahmawati; A Fahrur Rozi; Habib Filah Akbar Saputra (Prodi Ilmu Hukum Universitas Nahdlatul Ulama Indonesia, 2025)
The authority of the General Election Commission (KPU) to determine electoral districts and seat allocations in elections has experienced ups and downs. The Constitutional Court Decision No. 80/PUU-XX/2022 returns the authority of electoral districts and seat allocation to KPU absolutely through the General Election Commission Regulation (PKPU). This research aims to re-examine the authority of state institutions in the formation of electoral districts and the allocation of seats in elections through the scope of authority and the principle of institutional control (checks and balances). This research method uses a qualitative-library approach by examining normative law and legislation (statute approach), as well as related regulations. Primary legal materials are decisions and applicable laws and regulations, while secondary legal materials are books, scientific journals, and online news. The results of this study indicate that the arrangement of electoral regions and seat allocation is part of the KPU's authority as an Election Organiser based on the concept of administrative authority and state institutional principles.